A review of productive parameters, nutritive value and technological characteristics of farmed nutria meat (Myocastor coypus). (February 2019) - Saadoun, A.; Cabrera, M.C.
Abstract: The nutria ( Myocastor coypus ) is a prolific herbivorous rodent originating from southern South America. The nutria is farmed in many countries mainly for its pelt through selected animals called nutria "mutations", with different kinds of fur color and, up until now, nutria meat has been considered as a by-product. However, taking into account the growing interest of consumers to access novel and exotic meat, nutria meat could be proposed as an attractive and nutritional delicacy. The data presented in this review shows that the nutritional value of nutria meat is adequate for human nutrition, taking into account the protein content and amino acids composition. The fatty acids present in nutria meat are in line with health concerns for lipids nutrition in humans. Furthermore, the mineral composition of farmed nutria makes it a good source of iron, zinc, copper and selenium, all needed for human nutrition, especially iron when it comes to children and women. Highlights: The nutria ( Myocastor coypus ) is a rodent native to South America with a commercial live weight of 5–6 kg. Protein, amino acids content and fatty acids present in nutria meat are in line with human nutrition requirements. Nutria meat is a good source of iron, zinc, copper and selenium. Reported color, pH, and emulsion capacity of nutria meat, make it suitable for technological process. Nutria meat could be a good candidate to be offered as an attractive and nutritive delicacy.